Experimental study on post fire mechanical properties exhibited by S235JR and S355J2+N steel grades - Woźniczka, Piotr; Zajdel, Paulina (Archives of Civil Engineering, 2026)
The results of research on mechanical properties exhibited by typical structural steel grades S235 and S355 are presented in this paper. Each time the samples had been heated up to a predetermined temperature, cooled and subjected to a static tensile strength test. Several fire development scenarios and sample cooling scenarios had been considered. The maximum heating temperature reached during the research remained between 400◦C and 800◦C. The results of own experimental research have been compared against the recommendations found in bibliography regarding the reduction degree of mechanical properties exhibited by steel. The changes in the values of such parameters as the yield limit, tensile strength, modulus of elasticity and total limit elongation have been considered in the conducted analyses. Based on the results of this research new, temperature dependent, values of reduction coefficients for mechanical parameters of steel exhibited post fire have been determined. Two computational approaches have been applied for this purpose. In the first approach the reduction coefficients have been determined based on the minimum values obtained experimentally. In the second approach the characteristic and design values have been derived following the recommendations of the standard PN EN 1990. Both proposed sets of reduction coefficients may be applied when assessing the technical condition of a structure following a fire incident.